Tumor Mutation Burden Correlates With Efficacy of Chemotherapy/Targeted Therapy in Advanced Non–Small Cell Lung Cancer - Lin, Chen; Shi, Xun; Zhao, Jun; He, Qiong; Fan, Yun; Xu, Weizhen; Shao, Yang; Yu, Xinmin; Jin, Ying (Frontiers in Oncology, 2020)
Objectives: Accumulating evidence has illustrated greater benefit of immunotherapy in tumors with high tumor mutation burden (TMB), whereas its impact on targeted therapy or chemotherapy is undefined. Herein, we evaluated TMB outside of immuno-oncology in epidermal growth factor receptor (EGFR)–mutant patients and EGFR/ALK wild-type cohorts. Methods: In this retrospective study, we correlated TMB with response rate and progression-free survival (PFS) of patients who received EGFR–tyrosine kinase inhibitors (TKIs) or pemetrexed/platinum as first-line therapy. Tumor mutation burden was evaluated by targeted next-generation sequencing. Patients were divided into low (L)/intermediate (I)/high (H) TMB groups by tertiles. Results: In EGFR-mutant cohort, TMB-L patients had a massively improved PFS compared to TMB-I and TMB-H patients (16.4 vs. 9.0 vs. 7.4 months; log-rank p = 0.006) when treated with first-generation EGFR-TKIs. In EGFR/ALK wild-type cohorts who received pemetrexed/platinum regimen, the objective response rate (ORR) of TMB-L group was statistically superior than that of TMB-I and TMB-H groups (53.8% vs. 23% vs. 8.3%; log-rank p = 0.037), and patients with low TMB had a numerically but not significantly prolonged PFS (6.9 vs. 4.3 vs. 4.6 m; log-rank p = 0.22). Conclusion: Our data provide insights into the relevance between TMB and targeted/chemo therapy. Higher non-synonymous TMB correlates with inferior PFS for first-generation EGFR-TKIs in EGFR-driven patients and worse response to pemetrexed/platinum regimen in EGFR/ALK wild-type patients, which has potential clinical implications for cancer treatment but needs corroboration in larger studies.